Minimal hepatic encephalopathy – diagnosis and treatment - Wojciech Pisarek (Gastroenterology Review)
Hepatic encephalopathy is a dysfunction of the central nervous system caused by chronic and acute liver disease. It presents a wide spectrum of symptoms from undetectable in a standard clinical examination to hepatic coma. The mildest form of hepatic encephalopathy is minimal hepatic encephalopathy. It significantly influences the quality of life, prognosis, and the incidence of complications. A wide range of psychometric and neurophysiological tests are used in the diagnostics. Treatment is based on the same principles as in overt encephalopathy. The most commonly used drugs include rifaximin, ornithine aspartate, and LOLA.